Proprietary Methodology of Teaching Russian as a Foreign Language - Maksimovna Petrova, Svetlana (Opción, 2019)
The main objectives are as follows: to conduct a comparative analysis of the current state of teaching Russian as a foreign language; to describe the role of the graphical-symbolic analysis of a fictional work as a set of linguistic and artistic-pictorial resources forming a literary text in the system of teaching Russian as a foreign language; to prove the importance of the proprietary methodology including elements of graphical-symbolic analysis (based on semiotics, mnemonics and ergonomics) for foreigners compre- hending the ideological meaning of the fictional work under study, national traditions and customs, forming a sustainable interest in the Russian langua- ge; to determine the effectiveness of the above-mentioned proprietary methodology at different stages of teaching foreign students the Russian language (pre-university, Master’s Degree and postgraduate courses, as well as the system of academic mobility of foreign students). Foreign students take an active part in international academic competitions concerned with the study of the Russian language, "Diamond up your language" essay contests, become winners and awardees of student conferences (John Andersen from Guyana, Lưu Thị Huyền from Vietnam). The method of teaching foreign students the Russian language using the graphical-symbolic analysis of a fictional work is exemplified by I.S. Turgenev’s short story – "Bezhin Meadow". This writer was chosen not only because of his 200th anniversary (Novikova, 2015) celebrated in different countries around the world (The Order of the President of the Russian Federation No. 114, 2014), but also because of his contribution to the development of the Russian literature in the 19th century (Nedzvetsky, Poltavets, 2016), as well as the preservation of the Russian language. His literary works are analy- zed in numerous scientific studies (Polunina, Bauder, 2015). "Bezhin Meadow" (Lomakina, 2017) is an excellent learning material that helps foreign students understand the past era, the Russian traditions and customs described by the author, artistic and stylistic features of the Russian language starting from "... the sky overhanging it", "My heart sank", "I found myself on the edge of a horrible precipice" to nature description when the narrator meets children "It was a marvelous picture...", "... darkness was struggling with light", "The dark unclouded sky stood, inconceivably immense, triumphant, above us in all its mysterious majesty". While working with the text, foreign students begin to better understand the Russian language, its shades of meaning ("...One felt a sweet oppression at one’s heart, breathing in that peculiar, overpowering, yet fresh fragrance–the fragrance of a summer night in Russia"). Various means of visualization (slides, illustrations, the author’s portrait, etc.) help foreign students fully perceive the topic under study, which contributes not only to the development of their coherent speech, but also to a better understanding of Russia’s past and present.